Responding to Videos on Individual Struggle – An Analysis of Digital Empathy in Bilibili Comments - Sun, Ruixia; Bi, Shiwu (Technium Social Sciences Journal, 2024)
In an era dominated by digital technology, the study of empathy in digital environment has gained increasing attention. This paper has analyzed the comments responding to the interviews featuring grassroots’ struggle on a popular Chinese video-sharing platform Bilibili, and found that those comments expressing empathy can be categorized into three types according to the Interpersonal Reactivity Index: comments showing empathic concerns, comments demonstrating perspective-taking, and comments sharing similar personal stories. The paper discovered that, in the video-audience relationship, empathic comments turned to more description of similar self-experience than emotional concerns and perspective-taking in order to show understanding of other’s emotions. This paper has expanded the study of empathy based on post-comment interactions and added to the exploration of reading emotions in texts.